2011
DOI: 10.1177/1934578x1100600415
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan: From Biomimetic to Industrial Business Strategy

Abstract: Hyaluronan (hyaluronic acid) is a naturally occurring polysaccharide of a linear repeating disaccharide unit consisting of β-(1→4)-linked D-glucopyranuronic acid and β-(1→3)-linked 2-acetamido-2-deoxy-D-glucopyranose, which is present in extracellular matrices, the synovial fluid of joints, and scaffolding that comprises cartilage. In its mechanism of synthesis, its size, and its physico-chemical properties, hyaluronan is unique amongst other glycosaminoglycans. The network-forming, viscoelastic and its charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 183 publications
0
12
0
Order By: Relevance
“…This glycosaminoglycan has a high molecular weight (MW) distribution in human SF, ranging from 27 kDa to 10 MDa [ 12 14 ]. HA forms long nonsulfated chains of repeating disaccharides, comprising D-glucuronic acid and N-acetyl D-glucosamine, and provides SF with its high viscosity [ 9 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This glycosaminoglycan has a high molecular weight (MW) distribution in human SF, ranging from 27 kDa to 10 MDa [ 12 14 ]. HA forms long nonsulfated chains of repeating disaccharides, comprising D-glucuronic acid and N-acetyl D-glucosamine, and provides SF with its high viscosity [ 9 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The average 70 kg adult human body contains approximately 15 g of HA, of which one third is turned over every day [ 24 ]. This biopolymer is really outstanding among the natural hygroscopic (macro)molecules; during the process of water absorbance, high-molar-mass HA molecules swell in volume up to 1000 times in the form of polymer powder [ 24 , 25 , 26 , 27 ]. The biological effects of HA depend on their molar masses.…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronan-derived products have been used to maintain the structure of the eye’s capsule, mainly in the phacoemulsification (removal of the eye’s vitreous humor) step of cataract surgery, but also in other surgical procedures such as corneal transplantation, intraocular lens implantation, and vitreoretinal, anterior segment, and glaucoma surgery. Some biocompatible materials were introduced in the ophthalmic practice for the vitreous humor replacement after vitrectomy using a new crosslinked HA through adipic acid dihydrazide bridges [ 25 ]. It has been demonstrated that treatment with eye drops containing HA reduces oxidative stress in the conjunctiva of patients with dry eye disease [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The naturally occurring polysaccharide hyaluronic acid (HA) is a major component of the extracellular matrix and, additionally, it is found in the synovial fluid of joints and scaffolding that comprises cartilages. Peculiarly, one of its cellular receptors (CD44) it is found over expressed in many cancer cells [1,2]. Structurally, HA consists of β-(1→4)-linked D-glucopyranuronic acid and β-(1→3)-linked 2acetamido-2-deoxy-D-glucopyranose.…”
Section: Introductionmentioning
confidence: 99%